Pengembangan Media Pembelajaran Biologi Pokok Bahasan Ekosistem Guna Peningkatan Prestasi Siswa Kelas VII SMP Negeri 2 Sumbang - Windy Agus Setiasih; Dimara Kusuma Hakim (JUITA : Jurnal Informatika, 2012)
This study aims to establish a learning media of Biology subject on ecosystem to improve the students’ achievement for the seventh graders at SMP Negeri 2 Sumbang. Applications of learning media of Biology subject on ecosystem are built to provide facilities in the delivery of course material by providing a medium of learning more interesting, attractive and easy to understand. Making an application learning media of Biology subject on ecosystem is using the software Macromedia Flash 8. Test subjects consisted of 29 students. Stages of development of multimedia teaching Biology subject of the ecosystem through six steps, namely data collection, application design, application development, application testing, and implementation and maintenance of applications. The quality of the developed learning media viewed from the aspect of the content, learning, appearance, and the programming is good and the use of learning media of Biology subject on ecosystem impact both on student achievement is an increase in the average performance of 65.28 ± 7.73 to 74, 44 ± 5.23